Pengaruh Social Media Marketing, Price And Location Terhadap Customer Engagement Bengkel Motorsport Mifta Malang (Studi Kasus Pada Wirausaha Bengkel Motorsport Mifta Malang) - Mochamad Yuhdi Atoillah; Ronny Malavia Mardani; Andi Normaladewi (UNIVERSITAS ISLAM MALANG, 2023)
Abstr.Act’ This study aims to investigate the impact of social media marketing pricing and location on customer engagement on the Instagram social network, focusing on the Mifta Indonesia Motorsport workshop during 2022-2023. The research falls under the category of quantitative research, utilizing multiple linear regression as the primary method. The sampling technique employed is the Malhotra formula, which involves multiplying the number of variables by 5, resulting in 8.5 samples. To ensure the study's accuracy, various statistical tests were conducted, including validity tests, reliability tests, normality tests, multiple linear regression analysis, multicollinearity tests, alternative variance tests, F-tests, and t-tests. The results indicate that social media marketing effectiveness (X1), price (X2), and location (X3) collectively have a significant positive impact on customer engagement at Mifta Motorsport Indonesia workshops (Y). Keywords : Effect of Social Media, Price, Marketing, and Location on Customer Engagement